Incidencia de los factores de riesgo físicos en la seguridad y salud ocupacional del camal municipal cantón Junín - Bermeo Santana, Gema Guadalupe (2017)
The objective of the investigation was to evaluate the incidence of physical risk factors in the occupational health and safety of workers in the municipal district of Junín, talking as reference the legal basis of occupational safety and health in force in Ecuadorian legislation. It was performed as non-experimental research. Descriptive and documentary methods were used, using interview and survey techniques. The results showed that the risk that most affects them is the physical one, determining that the factors that are present in the different activities of the bovine and porcine slaughter processes are: temperature, illumination, noise and ventilation. They found 44 risk, of With 34% corresponding to noise, being the main risk factor that affects the workers at the time of their activities, followed by the high temperature (between 29 and 32.9°C ) with 23%, insufficient ventilation was found with18 %, excessive lighting with 14% and insufficient illumination with 11%. It was found among the 44 risk groups: nine moderate with 20%, 28 with 64% and seven intolerable, which represented 16% of the total risks. Based on the results, a health and safety program was developed for (S), which consisted of programs to minimize the physical irrigation factor, the first aid program, signaling, and training, in order to limit and mitigate the risks.